Proceedings of the 2015 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2015
DOI: 10.1145/2750858.2807519
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of artificial driving sounds for automated vehicles

Abstract: This version is available at https://strathprints.strath.ac.uk/54410/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Modal values were calculated for the emotion wheel variable. This follows the approach adopted by Beattie et al [2]. Table 2 shows the impact of stimuli intensity.…”
Section: Study 1 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modal values were calculated for the emotion wheel variable. This follows the approach adopted by Beattie et al [2]. Table 2 shows the impact of stimuli intensity.…”
Section: Study 1 Resultsmentioning
confidence: 99%
“…(Investigated in studies 1 and 2) RQ3: What effect does timing of thermal stimuli presentation have on the emotional perception of images? (Investigated in study 2) In the next two sections we review related work and provide an explanation of the equipment used for the two user studies. We then present our first user study procedure and results, followed by a description of our second user study and results.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that drivers quickly transitioned to the driving task for warnings that conveyed urgency, and performance was worst for unimodal visual alerts. Other work has looked at using auditory cues to provide drivers in autonomous vehicles awareness about the environment [5].…”
Section: (In-car) Alertsmentioning
confidence: 99%
“…In the post questionnaire drivers provided various scores for the different pre-alerts on a five-point scale with anchors for low (1) and high (5). In Figure 6 we present the histograms of the score for the metrics (1) annoyance, and (2) disruptiveness of the pre-alert.…”
Section: User Preferencesmentioning
confidence: 99%
“…The driving simulator study featured two driving conditions (manual and automated) and two auditory feedback types (Existing Vehicle Sounds and Spatial Earcons). Thus, participants undertook four driving scenarios following the procedure of Beattie et al [8]. During the manual conditions (NHTSA Level 0 [43]), participants controlled Open Driving Simulator (OpenDS) software via a steering wheel and pedals.…”
Section: Driving Taskmentioning
confidence: 99%